PENGARUH KEEFEKTIFAN PENGENDALIAN INTERNAL, KOMITMEN ORGANISASI, BUDAYA ETIS ORGANISASI DAN KETAATAN ATURAN AKUNTANSI TERHADAP FRAUD (STUDI EMPIRIS PADA ORGANISASI PERANGKAT DAERAH KABUPATEN SIAK) - Arnila, Tia; Basri, Yesi Mutia; Desmiyawati, Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to test and prove empirically influence the Effectiveness of Internal Control, Organizational Commitment, Ethical Culture Organization And Adherence to Accounting Rules Against Fraud (Empirical Study at the Organization of Regional Devices Siak District). The population in this research is all the existing OPD in Siak Regency in 2018. While the sample in this research is the OPD in siak district as much as 29 OPD. sampling technique using purposive sampling technique. Each OPD will be distributed as many as 5 questionnaires shown to the head of service, PPTK, head of the field, head of subsection finance and treasurer in Siak District so that the number of respondents in this study as many as 145 respondents. Data analysis method used is multiple analysis method with SPSS version 21.0. The results of the research show that the effectiveness of internal control, organizational commitment, organizational ethical culture and compliance with accounting rules have a significant negative effect on Fraud.Keywords: Effectiveness of Internal Control, Organizational Commitment, Organizational Ethical Culture, Adherence to Accounting Rules and Fraud